2020
DOI: 10.1002/jsfa.10910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tri‐frequency ultrasound‐ethanol pretreatment combined with infrared convection drying on the quality properties and drying characteristics of scallion stalk

Abstract: BACKGROUND Having short drying time and attractive product quality are important in fruit and vegetable dehydration processing. In this work, tri‐frequency (20, 40 and 60 kHz) ultrasound‐ethanol pretreatment, ultrasound‐water pretreatment and ethanol pretreatment were employed before infrared convection drying (ICD) of scallion stalks, which was aimed at improving the drying process and quality of the end products. The mass transfer, drying characteristics (moisture ratio and drying rate and quality properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…On the other hand, a higher rehydration ratio was observed at higher ethanol concentration, higher citric acid concentration, and higher blanching temperature except higher US power ( p < .05). Similar reports were published by Doymaz (2014), Sahin and Doymaz (2017), Doymaz et al (2015), Doymaz and Sahin (2016), Doymaz and Bilici (2014), and Doymaz (2020) for citric acid and blanching pretreatments; Rojas et al (2020), Rojas et al (2020), Rojas et al (2018), and Zhou et al (2021) for ethanol pretreatment; Bozkır et al (2019) and Zhang et al (2016) for US pretreatment. Effect of citric acid and blanching on rehydration ability may be explained with more cell permeability and inactivation degradative enzymes.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…On the other hand, a higher rehydration ratio was observed at higher ethanol concentration, higher citric acid concentration, and higher blanching temperature except higher US power ( p < .05). Similar reports were published by Doymaz (2014), Sahin and Doymaz (2017), Doymaz et al (2015), Doymaz and Sahin (2016), Doymaz and Bilici (2014), and Doymaz (2020) for citric acid and blanching pretreatments; Rojas et al (2020), Rojas et al (2020), Rojas et al (2018), and Zhou et al (2021) for ethanol pretreatment; Bozkır et al (2019) and Zhang et al (2016) for US pretreatment. Effect of citric acid and blanching on rehydration ability may be explained with more cell permeability and inactivation degradative enzymes.…”
Section: Resultssupporting
confidence: 81%
“…Similarly, reduction in drying time in potatoes with ethanol pretreated was notified by Guedes et al (2021). Zhou et al (2021) reported higher DR in scallion stalk pretreated with ethanol solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…pretreated for 5-60 min)(Carvalho, Rojas, Silveira, & Augusto, 2020;Rojas & Augusto, 2018a, 2018b, apple (pretreated for 5 s to 30 min)(Amanor-Atiemoh et al, 2020;Rojas, Augusto, & Cárcel, 2020;Rojas, Augusto, & Cárcel, 2021;Zubernik, Dadan, Cichowska, & Witrowa-Rajchert, 2019), potato (pretreated for 3-15 min), carrot (pretreated for 5 s to 30 min)(Dadan & Nowacka, 2021;Santos, Guedes, Rojas, Carvalho, & Augusto, 2021), melon (pretreated for 10 min)(da Cunha et al, 2020), garlic (pretreated for 30 min)(Feng et al, 2019) and scallion stalk (pretreated for 5-30 min)(Wang et al, 2019;Zhou et al, 2020). On the other hand, and similarly to the present work, the ethanol pretreatment did not influence the drying process of pineapple pomace(Bitencourt, Carvalho, Corrêa, & Augusto, 2020), which was attributed to the sample structure and composition.…”
mentioning
confidence: 99%